2015
DOI: 10.1177/8756087915569097
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the effects of organomodified-fluoromica on mechanical and barrier properties of compatibilized high density polyethylene nanocomposite films

Abstract: Nanocomposite sheets based on high density polyethylene and containing organically modified fluoromica and three different compatibilizers (ethylene vinyl acetate copolymer and two maleic anhydride grafted high density polyethylene (HDPE-g-MA) grades with different melt flow indices) were prepared by melt mixing processing in an internal mixer. In order to evaluate the direct relationship between different properties of compression molded sheets and their microstructures, mechanical and barrier properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
0
8
0
1
Order By: Relevance
“…[9,16] It has proven that nanometer sized particles play a common role of compatibilizers in polymeric blends along with the reinforcing role. [3,17,[31][32][33] Since the absorbed chains on the nanoclay surfaces and galleries have slower molecular movements, PE/EVA/nanoclay systems have comparatively slower phase separation during the cooling stage of the melt process. As a direct result, partial miscibility and mutual solubility of PE/EVA phases enhance in the presence of nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9,16] It has proven that nanometer sized particles play a common role of compatibilizers in polymeric blends along with the reinforcing role. [3,17,[31][32][33] Since the absorbed chains on the nanoclay surfaces and galleries have slower molecular movements, PE/EVA/nanoclay systems have comparatively slower phase separation during the cooling stage of the melt process. As a direct result, partial miscibility and mutual solubility of PE/EVA phases enhance in the presence of nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…The processing temperature, PE/EVA phase miscibility and dispersion and localization states of nanoparticles changes the crystallization behavior of the polymeric components. [1,9,17,32] On the other hand, it has been verified that the interfacial interactions of PE/EVA mixtures are strongly dependent on the blend composition and change by the phase inversion. It has been reported that the PE-rich blends have positive deviations from the predicted results of mixture rule, while the EVA-rich blends show a negative deviation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 In such operations (extrusion, compression or injection molding, thermoforming and others) flake orientation is achieved as flakes tend to orient along the prevailing flow field – either in the main flow direction with shear flow or transverse to it with extensional flow. Special care is therefore needed in designing polymer processing equipment for a desired flake orientation, 21 and even then, it is possible that, when it comes to “on-site” use, not all flakes will be oriented perpendicular to the macroscopic diffusion direction. 19,20 Even when the final average orientation is the desired one, not all flakes end up oriented in the desired direction, but instead have a distribution of orientations.…”
Section: Introductionmentioning
confidence: 99%
“…INTRODUCCIÓN El polietileno de alta densidad (HDPE) es utilizado en muchas aplicaciones comerciales debido a su versatilidad en propiedades físicas, mecánicas, resistencia química a solventes, propiedades de barrera y buena procesabilidad. Por tal motivo, ha existido el interés en reforzarlos con aditivos minerales tales como carbonato de calcio [1], arcillas [2], sílice [3], mica [4] entre otros, para incrementar el rango de sus aplicaciones industriales. Debido a las características intrínsecas únicas y su relativo bajo costo, las arcillas han sido incorporadas en bajas proporciones a los polímeros desarrollando nanocompuestos obteniendo mejoras considerables en el desempeño de los polímeros en general [5].…”
unclassified